Pendidikan Kesehatan dalam Pencegahan dan Penularan Penyakit DBD pada Anak-Anak di Kampung Benteng - Yuda Nugraha; Akmal Rahayu Dasuki Rahmat; Triman Tresnawan (KOLABORASI JURNAL PENGABDIAN MASYARAKAT, 2022)
Introduction: Dengue hemorrhagic fever (DHF) is caused by Aedes albopictus and Aedes aegypti mosquitoes which carry the Dengue virus which is spread through their bites, where these mosquitoes are very happy to be in tropical areas like Indonesia, which has a tropical climate so it is very vulnerable, especially for children. at an early age as well as for adults to be attacked by Aedes aegypti and Aedes albopictus mosquitoes that cause dengue fever. Objective: After conducting health education on prevention of dengue hemorrhagic fever, children can understand or know about the disease, symptoms, and prevention of dengue hemorrhagic fever. Method: starting with a survey or looking for a strategic place for the implementation of activities, followed by an assessment or collection of appropriate information or data in the presentation of the given title, after getting the right title then the author prepares materials for the implementation of the main event. after that coincided on January 21, 2022, a counseling event was held and followed by an evaluation by giving questions or asking questions about the material that had been given. Result: From the provision of health education to children, it produces great enthusiasm, especially when giving questions and answers to children when the evaluation takes place so that it can be interpreted that children understand clearly about dengue prevention with success and it is implemented. Conclussion: with this, it is highly expected that the number of infected with dengue fever will decrease so that health in Indonesia is especially better year after year, by regularly conducting health education to various regions in the country.